Dual‐grained (Ti, W)C–Ni cermets by two‐step carbonization: Hot isotropic press sintering of NiTiW alloys and colloidal graphite. Issue 7 (24th December 2018) - Xiong, Huiwen; Wen, Yu; Li, Zhiyou; Zhou, Kechao
Abstract: Reactive sintering of crushed metals and carbon is advantageous for preparing toughened complete solid‐solution cermets (CSCs). Here, dual‐grained (Ti0.6, W0.4 )C–18Ni cermets were prepared using a two‐step carbonization method. High‐energy milling of Ni–Ti–W–C (Ni(Ti0.6, W0.4 )4 C) mixture afforded NiTiW solid solution, which was then transformed into Ni6 W6 C by heating at 1250°C. Twinned (Ti, W)C platelets were formed by the carbonization of Ni2 W4 C during liquid sintering. W atoms that accumulated in the (111) planes of TiC promoted the {111} twin formation, leading to sandwich‐type (Ti, W)C platelets. Dense (Ti0.6, W0.4 )C–18Ni cermets were obtained by hot isostatic press sintering in Ar with satisfactory Hv of 12.8 ± 0.2 GPa, high strength of 1960 ± 84 MPa and toughness of 15.80 ± 0.6 MPa·m 1/2 . A higher sintering temperature or graphite content accelerated the carbonization, resulting in coarser platelets with decreased aspect ratio. This study provides a new approach to modify the microstructure of CSCs and a method for preparing dual‐grained cermets.